Oversight Effectiveness and Political Will : Some Lessons from West Africa - Pelizzo, Riccardo; Stapenhurst, Rick (Taylor and Francis, 2013)
The purpose of the present note is to advance two theoretical claims. The first claim proposed is that the impact of the availability of oversight tools and of the most broadly understood legislative capacity (availability of material, technical, financial resources; availability of well-trained staff) on the effectiveness with which legislative oversight is performed is conditional. The second claim put forward, after reviewing a rich body of work on executive–legislative relations and legislative oversight in West Africa, is that, of the various conditions that promote or prevent the effective use of oversight tools and capacity, political will is the single most important. These claims have both theoretical and practical relevance, for if political will is as important as is claimed for the effective performance of the oversight function, then international organisations may have to reconsider their approach to legislative strengthening.